(untitled) (Universal International Scientific Journal, 2026)
This article examines the development of speech and linguistic competencies among students in schools where instruction is conducted in the Tajik language, based on Jim Cummins’ theory of bilingualism. Specifically, the principles of BICS (Basic Interpersonal Communicative Skills) and CALP (Cognitive Academic Language Proficiency) are utilized to analyze students’ communicative abilities partially developed within their socio-natural environments. The study explores how these competencies are integrated into current curricula and textbooks, while also highlighting the methodological foundations for leveraging students’ existing speech experiences to foster linguistic competence